Low water level drives high nitrous oxide emissions from treatment wetland. (15th June 2022) - Kasak, Kuno; Kill, Keit; Uuemaa, Evelyn; Maddison, Martin; Aunap, Raivo; Riibak, Kersti; Okiti, Isaac; Teemusk, Alar; Mander, Ülo
Abstract: Wetlands that are restored for carbon sequestration or created for water treatment are an important sources of greenhouse gases, especially methane. The emission of nitrous oxide (N2 O) from these systems is often considered negligible due to the inundation and anerobic conditions that support complete denitrification. We used closed chamber method to analyze N2 O fluxes over a long-term period across heterogeneous wetland ecosystem constructed for treating nitrate-rich agricultural runoff. Our results showed that the water depth and temperature were most important factors affecting high N2 O emissions. The shallow areas where water depth was less than 9 cm created N2 O hot spots that emitted 48.8% of the total wetlands annual emission while only covering 6% of the total area. The annual emission from shallow-water hot spots with dense helophytic vegetation was 4.85 ± 0.5 g N2 O–N m −2 y −1 while it was only 0.37 ± 0.01 g N2 O–N m −2 y −1 in deeper zones. While the water depth was the main factor for high N2 O emissions, the temperatures increased the magnitude of the flux and therefore summer droughts and water drawdown created even larger hot spots. These results also suggest that IPCC benchmarks could underestimate N2 O emission from shallow waterbodies. Thus, it is important that the shallow zones and water level drawdown in the created or restored wetlands is avoided to minimize the N2 O flux. Highlights: Low water level is the main driver for high N2 O emission in treatment wetland. Temperature will control the magnitude of N2 O flux in shallow water areas. Increased water level reduced significantly N2 O emission from shallow zones.